Alimentary preconditioning in Acromyrmex subterraneus brunneus workers - Camargo, Roberto S. [UNESP]; Lopes, Juliane F. [UNESP]; Forti, Luiz Carlos [UNESP]; De Matos, Carlos Alberto O. [UNESP]; De Andrade, Ana Paula P. [UNESP] (My University, 2003)
Ants suffer a strong environmental influence and are sometimes conditioned for many social activities. To understand better this phenomenon in leaf-cutting ants, 24 colonies of Acromyrmex subterraneus brunneus (Hymenoptera: Formicidae) were conditioned for 2 months with 6 different plants (Citrus spp., Ligustrum spp., Acalypha spp., Eucalyptus spp., Alchornea triplinervia, Melia spp.), to verify alimentary preconditioning in plant selection. After the conditioning period, plants were offered simultaneously, to evaluate the acceptability of each plant species. During foraging, the workers did not exhibit alimentary source fidelity, which was familiarized. This fact suggests the absence of alimentary preconditioning, reinforcing the polyphagic foraging behavior of leaf-cutting ants.
Keywords: Acromyrmex subterraneus brunneus; Behavior; Foraging; Leaf-cutting ants; Acalypha; Acromyrmex; Acromyrmex subterraneus; Alchornea; Atta; Citrus; Eucalyptus; Formicidae; Hymenoptera; Ligustrum; Melia; Meliaceae